2016
DOI: 10.15406/jpnc.2016.04.00154
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Tongue Tie: The Effectiveness of Intervention

Abstract: The promotion of breastfeeding is a major public health concern. The World Health Organisation and UNICEF express the importance of breastfeeding up to two years and beyond. Tongue tie is identified in the literature as abnormally short frenulum which can lead to breastfeeding difficulties such as attachment, nipple pain and damage. Tongue tie is viewed by the Baby friendly hospital initiative (BFHI) as a readily treatable cause for breastfeeding difficulties. This review aimed to identify if the intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In a study done in USA, in the University of Cincinnati published in 2002 there is a total prevalence of tongue tie in 18% of the total children population. In the UK, a study done at the Southhampton General Hospital showed tongue tie in 10% of the babies born there 7 . In the Indian scenario 12 babies per 1000 are affected by tongue tie according to a recent study in 2008.…”
mentioning
confidence: 99%
“…In a study done in USA, in the University of Cincinnati published in 2002 there is a total prevalence of tongue tie in 18% of the total children population. In the UK, a study done at the Southhampton General Hospital showed tongue tie in 10% of the babies born there 7 . In the Indian scenario 12 babies per 1000 are affected by tongue tie according to a recent study in 2008.…”
mentioning
confidence: 99%